Aktualne problemy edukacji uczniów z niepełnosprawnością w percepcji nauczycieli w różnych formach kształcenia specjalnego - Lipińska-Lokś, Jolanta (Kultura-Społeczeństwo-Edukacja, 2015)
Education of students with disabilities is a challenge for teachers engaged in various forms of special education. Due to recognizing the limitations and problems connected with education of such a diverse group of students, new solutions are sought.This article compares the higher education systems between China and Ukraine.